PENGARUH MOTIVASI INTRINSIK, GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DINAS PETERNAKAN KABUPATEN ASAHAN - Fazri Akbar Damanik; Surya Bakti (Smart Education, 2026)
This study aims to determine the simultaneous and partial influence of intrinsic motivation, transformational leadership style and compensation on performance. The number of samples was 31 respondents. The data analysis technique used multiple linear regression. The regression results produced the equation Y = 10.936 + 0.402X1 + 0.395X2 + 0.262X3. The F-test produced a value of F count (20.595) > F table (2.96), meaning that intrinsic motivation, transformational leadership style and empowerment have a simultaneous influence on performance. The results of the t-test, partially intrinsic motivation has a positive effect on performance because t count (2.297) > t table (2.04841), transformational leadership style has a positive effect on performance because t count (3.554) > t table (2.04841), its influence has a positive effect on performance because t count (2.011) > t table (2.04841). The R2 test results showed an adjusted R Square value of 0.638, indicating that the independent variables, consisting of intrinsic motivation, transformational leadership style, and fulfillment, were able to explain 63.8% of performance, while the remaining 36.2% was explained by other variables not included in this study.